2005
DOI: 10.4315/0362-028x-68.6.1198
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Escherichia coli O157:H7 Infections Associated with Nonintact Blade-Tenderized Frozen Steaks Sold by Door-to-Door Vendors

Abstract: Steaks have not been recognized as an important vehicle of Escherichia coli O157:H7 infection. During 11 to 27 June 2003, the Minnesota Department of Health (MDH) identified four O157 infection cases with the same pulsed-field gel electrophoresis (PFGE) subtype. All four case patients consumed brand A vacuum packed frozen steaks sold by door-to-door vendors. The steaks were blade tenderized and injected with marinade (i.e., nonintact). Information from single case patients in Michigan and Kansas identified thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 17 publications
0
38
0
1
Order By: Relevance
“…The specific risk factors noted do, however, provide numerous clues or starting points for secondary interviews of cases where the use of specific questions could more effectively identify or eliminate suspected sources. This type of approach has proven useful in interviews to identify sexual partners (5), is part of the cognitive interview technique used in criminal investigations (22), and is being applied to food-borne disease investigations (18). PFGE cluster N (Sm0046:Kp0026) is indistinguishable from a familial common-source outbreak linked to precooked sausages distributed by a particular butcher in Christchurch (14).…”
Section: Discussionmentioning
confidence: 99%
“…The specific risk factors noted do, however, provide numerous clues or starting points for secondary interviews of cases where the use of specific questions could more effectively identify or eliminate suspected sources. This type of approach has proven useful in interviews to identify sexual partners (5), is part of the cognitive interview technique used in criminal investigations (22), and is being applied to food-borne disease investigations (18). PFGE cluster N (Sm0046:Kp0026) is indistinguishable from a familial common-source outbreak linked to precooked sausages distributed by a particular butcher in Christchurch (14).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies reported in India indicated the incidences of foodborne diseases, wherein the food implicated were sandwiches [10], soybean milk [11], stale rice [12], chicken [13], bread and vegetable curry, and butter milk [14], where as studies in other countries indicated the incidence of foodborne diseases wherein the foods implicated were Beef [15], Pork meat [16], frozen steaks [17], poultry, and other meat items [18]. Outbreak of food poisoning may be attributed to the type of food being consumed, which is based on the food habits of the people specific to the country problems associated during transport, climatic conditions, food storage, and awareness about food safety concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Swanson et al 33 identified failure in effective cooking of mechanically tenderized raw or partially cooked beef product as a significant factor in related outbreaks.…”
Section: Control Strategies and Labeling Requirementsmentioning
confidence: 99%